2022
DOI: 10.1038/s12276-022-00812-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation by histone-modifying enzymes under hypoxic conditions: a focus on histone methylation and acetylation

Abstract: Oxygen, which is necessary for sustaining energy metabolism, is consumed in many biochemical reactions in eukaryotes. When the oxygen supply is insufficient for maintaining multiple homeostatic states at the cellular level, cells are subjected to hypoxic stress. Hypoxia induces adaptive cellular responses mainly through hypoxia-inducible factors (HIFs), which are stabilized and modulate the transcription of various hypoxia-related genes. In addition, many epigenetic regulators, such as DNA methylation, histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 123 publications
1
18
0
Order By: Relevance
“…The highly selective N‐methylation at the sp 3 nitrogen atoms of α‐amino acid motifs demonstrated in the present N‐methylation system implies great potential for its application in the selective synthesis of N‐methylated bioactive peptides [1,2] and epigenetic modification of proteins (histones) [9–12] . As a preliminary study for such an application, N‐methylation reactions using dipeptides (Gly‐Gly: 1 u and Gly‐ l ‐Ala: 1 v ) were carried out.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The highly selective N‐methylation at the sp 3 nitrogen atoms of α‐amino acid motifs demonstrated in the present N‐methylation system implies great potential for its application in the selective synthesis of N‐methylated bioactive peptides [1,2] and epigenetic modification of proteins (histones) [9–12] . As a preliminary study for such an application, N‐methylation reactions using dipeptides (Gly‐Gly: 1 u and Gly‐ l ‐Ala: 1 v ) were carried out.…”
Section: Resultsmentioning
confidence: 93%
“…The highly selective N-methylation at the sp 3 nitrogen atoms of α-amino acid motifs demonstrated in the present Nmethylation system implies great potential for its application in the selective synthesis of N-methylated bioactive peptides [1,2] and epigenetic modification of proteins (histones). [9][10][11][12] As a preliminary study for such an application, N-methylation reactions using dipeptides (Gly-Gly: 1 u and Glyl-Ala: 1 v) were carried out. Dimethylation at the N-terminals gave the corresponding products in good to excellent yields (2 u: 83%, 2 v: 94%, entries 22 and 23), while the peptide bonds and CO 2 H remained intact.…”
Section: %mentioning
confidence: 99%
“…However, unlike histone acetylation, the regulation effects of histone methylation depend on the methylation site. For example, methylation of H3K4, H3R17 and H3K36 were found in transcriptionally active regions, whereas methylation of H3K9, H3K27 and H4K20 were found in transcriptionally repressed regions [ 61 ]. Recent studies showed that HFD could significantly increase the histone H3 trimethylation at lysine 4 (H3K4Me3) [ 62 ] while increased H3K4Me3 level at the interleukin 6 ( Il-6 ) promoter region could promote its expression which subsequently contributed to lung fibrosis through enhancing EMT [ 63 ].…”
Section: Epithelial Cell Injury and Abnormal Activationmentioning
confidence: 99%
“…For instance, proteins containing N-methylated -amino acid residues have great potential for biochemical application in proteomics 51 and epigenetics. 52 The structures of 25au, 25av, 25aw, 25ay, and 25bg are found in naturally occurring compounds with potent bioactivity. Compound 25bl′ has an N-methyl N,Sacetal structure available in the Kent ligation.…”
Section: Account Synlettmentioning
confidence: 99%